2012
DOI: 10.1108/17542431211228629
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual framework for police deviance applied to police crime court cases

Abstract: Purpose -A conceptual framework for police deviance and crime has recently been suggested and presented by other scholars. This research attempts to test the framework empirically based on court cases where police employees were prosecuted and convicted.Design/methodology/approach -The sliding slope in the conceptual framework was separated into two dimensions, motive and damage, respectively. Court cases were coded according to these dimensions.Findings -Empirical results provide support for the framework by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…In line with prior studies (Gottschalk, 2012b;Hesselink & H€ aefele, 2015;Stinson, Todak et al, 2015), and by using a multilevel modeling strategy, the current study found that on-duty female officers were more likely to commit economic crime and drug-related crime when controlling for both individual characteristics and agency background. Although further studies would be needed to identify the specific reasons behind the slippery slope process associated with serious misconduct, we argue that corrupt police behavior is primarily related to personal gain (Gottschalk, 2012b) or personal changes (Hsieh & McShane, 2021), rather than being compelled by external forces, coercion, or others when on-duty. Although it may be beyond the scope of the current study, the findings here could possibly be explained by Simon's (1975) opportunity thesis, which postulates that as women make inroads into diverse positions, jobs, and occupations, they are presented with more channels and opportunities for deviance, misconduct, corruption, and crime.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…In line with prior studies (Gottschalk, 2012b;Hesselink & H€ aefele, 2015;Stinson, Todak et al, 2015), and by using a multilevel modeling strategy, the current study found that on-duty female officers were more likely to commit economic crime and drug-related crime when controlling for both individual characteristics and agency background. Although further studies would be needed to identify the specific reasons behind the slippery slope process associated with serious misconduct, we argue that corrupt police behavior is primarily related to personal gain (Gottschalk, 2012b) or personal changes (Hsieh & McShane, 2021), rather than being compelled by external forces, coercion, or others when on-duty. Although it may be beyond the scope of the current study, the findings here could possibly be explained by Simon's (1975) opportunity thesis, which postulates that as women make inroads into diverse positions, jobs, and occupations, they are presented with more channels and opportunities for deviance, misconduct, corruption, and crime.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, this study observed that young female officers were less likely to commit drug crimes compared to older officers, which was inconsistent with Donner and associates' (2016) study that reported that demographic background did not affect police misconduct. Still, the current findings could possibly bolster the rotten apple argument that problematic police behavior stems from individual characteristics rather than systemic corruption (Gottschalk, 2012b).…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations